The Epidemiology and Outcome of Biliary Atresia: Saudi Arabian National Study (2000-2018) - Abdulrahman Al-Hussaini; Abdulrahman Al-Hussaini; Abdulrahman Al-Hussaini; Mohammed Abanemai; Homoud Alhebbi; Omar Saadah; Razan Bader; Razan Bader; Ahmed Al Sarkhy; Maher Alhatlani; Hana Halabi; Ahmed Aladsani; et al. (Frontiers Media S.A., 2022)
BackgroundThe epidemiology and outcomes of biliary atresia (BA) have been well-documented in national cohorts from two main ethnicities, namely, the Asian Orientals and Caucasians, with incidence ranging from 1 in 5,000 to 1 in 9,000 live births in East Asia and 1 in 15,000 to 19,000 live births in Europe and North America.ObjectiveWe report the first nationwide BA study outside North America, Europe, and East Asia to describe the epidemiology and outcomes of BA in Saudi Arabia.MethodsA national database of BA cases diagnosed between 2000 and 2018 was analyzed. We assessed clearance of jaundice (bilirubin <20 μmol/L) in all cases that underwent Kasai portoenterostomy (KPE). We then estimated survival using the Kaplan-Meier method with endpoints of liver transplantation (LT), death, or survival with native liver (SNL).ResultsBA was diagnosed in 204 infants (106 females; 10% pre-term). The incidence of BA was 1 in 44,365, or 2.254 in 100,000 live births (range, 0.5-4 in 100,000). Polysplenia was diagnosed in 22 cases (11%). The median age at referral was 65 days. A total of 146 children (71.5%) underwent KPE at a median age of 70 days. Clearance of jaundice was achieved in 66 of the 146 (45%) infants. The 10-year SNL after KPE was 25.5%, and the overall 10-year estimated survival was 72.5%. The Kaplan-Meier survival curves for patients undergoing KPE at the age of <60, 61-90, and >90 days showed a SNL rate at 51.6, 33, and 12.5%, respectively, at 5 years (P < 0.001). The 2-, 5-, and 10-year post-LT survival rates were 92.5, 90.6, and 90%, respectively. Undergoing an initial KPE did not impact negatively on the overall LT survival rate when compared to BA cases that underwent primary LT (P = 0.88).ConclusionThe incidence rate of BA in Saudi Arabia is lower than the incidence reported elsewhere. Late referral of BA cases remains a problem in Saudi Arabia; as a result, the SNL rate was lower than reported by other national registries. Hence, national policies devoted to timely referral and earlier age at KPE are needed.